Experience of one hundred cases of ASD closure - Reddy, Jaypal; Sah, Bijay (Journal of College of Medical Sciences-Nepal, 2016)
jdjd Background & Objectives: Atrial Septal Defect is a common congenital heart disease and surgical closure is the treatment of choice in many cases. This article presents the diagnostic criteria, surgical technique and postoperative management of hundred consecutive patients operated by a single surgeon at single centre. Materials and methods: One hundred (100) patients having atrial septal defect (ASD) underwent surgery at Osmania General Hospital, OMC, Hyderabad between January 1990 and October 1998. Sixty eight percentages (68%) of the patients were females and 32% of the patients were male. Fifty nine percentages (59%) of patients were in the age group of 11-30 yrs. Majority of the patients (70%) were symptomatic and were in NYHA class II. 'O' Rh-positive blood group was found in 35% of patients. Associated cardiac lesions were present in 28% of cases. One case each of Cortriatrium, Lutembacher's syndrome and Holt-Oram syndrome were present in this series. Eighty nine percentages (89 %) were moderate sized defects repaired by direct closure where as rest of 11% needed patch repair. Cold crystalloid cardioplegia with moderate hypothermia (28°C) was employed in 83 cases, ventricular fibrillation at normothermia in 5 cases and normothermic warm blood cardioplegia with continuous perfusion of coronary arteries in 12 patients. Results: Total duration of cardiopulmonary bypass ranged from 21 minutes to 100 minutes (mean duration 54.4 minutes) and aortic cross clamp time ranged from 10 minutes to 68 minutes (mean duration 22.9 minutes). Blood transfusion requirement ranged from 1 unit to 10 units (mean 3.1 units). There was no hospital death. Postoperative complication rate was 15%. Conclusion: Atrial septal defect closure is a safe, simple and effective operation with excellent long term results. Journal of College of Medical Sciences-Nepal, Vol.11(4) 2015: 9-13